Productivity efficiency analysis of the airlines in China after deregulation. (January 2015) - Cao, Qian; Lv, Jinfeng; Zhang, Jun
Abstract: Using data envelopment analysis and the Malmquist productivity index, this paper studies productivity efficiency of various airlines in China after the Chinese government deregulated the aviation industry in 2005. The results show that the productivity efficiency of non-state-owned airlines improves rapidly and eventually exceeds state-owned airlines after the deregulation policy. Among the state-owned airlines, the productivity of the local airlines and their technical changes are better than those of the central airlines. Highlights: We introduce the process of institutional change of China's civil aviation industry from 1949 to 2010. According to the nature of ownership, we divide the Chinese airlines into three categories. We use DEA and the Malmquist productivity index to analyze productivity efficiency of these three types of airlines after the Chinese government deregulated the aviation industry in 2005.